Faculty Development and Documenting Teaching Effectiveness in Online Classes - Margaret A Thomas-Evans; Markus Pomper (Academic Chairpersons Conference Proceedings, 2015)
Online programs and courses require different strategies for faculty development and documenting success in teaching than face-to-face classes. Department chairs play a crucial role in facilitating this aspect of faculty development. The presenters will discuss strategies for faculty professional development in two departments with different academic foci: English and mathematics.
Keywords: Teaching online; developing online classes; documenting effectiveness of online classses